New Mexico’s Faustian Bargain with Science: Balancing Pride, Greed and Fear - Lucie Genay (Current Objectives of Postgraduate American Studies)
This article is an account of the emotional heritage of the scientific revolution which dramatically transformed the state of New Mexico into a nuclear Eldorado. The local populations accepted what turned out to be a Faustian bargain in which they sacrificed more or less knowingly their land, traditions and environment for the economic benefits of a new industry based on the offspring of the world's first atomic laboratory in Los Alamos.